Comparison of DKRZ Database and LARS-WG Model in Three Parameters of Minimum Temperature, Maximum Temperature and Precipitation (Case study: Qazvin plain) - Fatemeh Borzoo; Hadi Ramezani Etedali; Abbas Kaviani (Nīvār)
Improving agriculture, water resources management, flood management, and preventing environmental damage in future periods requires predicting climate data and adapting management and macro decisions to these changes. Today, it is possible to predict this data by using models and web databases. For this purpose, in the present study, the data obtained from the web database DKRZ and LARS-WG model, under three variables (minimum temperature, maximum temperature and precipitation) of Qazvin plain in five public circulation models of the fifth IPCC report (EC-EARTH, GFDL-CM3, HadGEM2-ES, MIROC5, MPI-ESM-MR) under two release scenarios (4.5 and 8.5) in future periods (2021-2040, 2041-2060, 2061-2080, 2081) -2100 and 2021-2100) were calculated and compared. The differences of the variables in each period compared to their mean in the base period (1991-2020) were examined. The highest and lowest rates of climatic variables during future periods and the general circulation model of the atmosphere and its scenario were introduced. In the period 2021-2100, LARS-WG-RCP4.5, LARS-WG-RCP8.5 and DKRZ-RCP8.5 models, 0.65, 0.8, 0.63° C increase the minimum temperature compared to the base period and DKRZ- RCP4.5 reports 0.61° C minimum temperature decrease compared to baseline. LARS-WG models predict maximum temperature rise under scenarios of 4.5 and 8.5, 0.75 and 0.86° C. DKRZ database models under maximum scenarios of 4.5 and 8.5 report maximum temperature drop of 2.53 and 1.16° C, respectively. According to the results of the models, the precipitation is LARS-WG-RCP4.5, LARS-WG-RCP8.5, DKRZ-RCP4.5 and DKRZ-RCP8.5, 16/35, 24/13, 146 and 145/97 mm, respectively. It increases in value in the base period.